Comparison of Hydrocortisone Continuous Rate Infusion and Prednisolone or Dexamethasone Administration for Treatment of Acute Hypoadrenocortical (Addisonian) Crisis in Dogs - Mitropoulou, Athanasia; Häuser, Mia-Katharina; Lehmann, Hendrik; Hazuchova, Katarina (Frontiers in Veterinary Science, 2022)
Objectives: To determine whether administration of intravenous hydrocortisone is a safe and effective alternative treatment in comparison to the traditional treatment with prednisolone/dexamethasone in dogs presenting with Addisonian crisis; and to assess if there is any advantage of the former over the latter in normalisation of electrolyte imbalances and in hospitalisation length in these dogs. Methods: Medical records of client-owned dogs with hypoadrenocorticism were retrospectively reviewed. Time until normalisation of sodium and potassium concentration, intravenous fluid needs over the first 24 hours and hospitalisation length were compared between hydrocortisone and prednisolone/dexamethasone treated dogs. Results: Twenty-five dogs met the inclusion criteria; 13 received hydrocortisone and 12 prednisolone/dexamethasone. Intravenous hydrocortisone was well tolerated but failed to prove superiority in terms of time to normalisation of sodium and potassium concentration. Interestingly, potassium normalised in all dogs prior to discharge, but sodium did not in 1/11 hydrocortisone and 5/9 prednisolone/dexamethasone treated dogs with initial hyponatraemia (p=0.05). Hydrocortisone treated dogs, however, had more electrolyte re-checks (hydrocortisone treated dogs, median (range): 4 (2 – 16); prednisolone/dexamethasone treated dogs: 2 (0 – 6); p=0.001). There was no difference in intravenous fluid needs over the first 24 hours but hydrocortisone treated dogs had longer hospitalisation (hydrocortisone: 81 (45 – 309) hours; prednisolone/dexamethasone: 52 (22 -138) hours; p= 0.01). Clinical Significance: Intravenous hydrocortisone is well tolerated and safe, but no clear additional benefit over traditional glucocorticoid replacement could be identified. Also, it might result in longer hospitalisation time and more intensive monitoring.